Outcomes of forensic psychiatric observation among alleged sexual offenders referred to Thabamoopo Hospital, Limpopo - Ngwenya, Thembani Advocate (My University, 2022)
BACKGROUND: The challenge of sexual offence crimes against women and children is notably increasing worldwide with an accompanying impact on the mental and physical well-being of the victims and society, in general. Despite the impact, sexual offenders remain a complex group, not well studied in forensic psychiatry settings globally. Previous studies identify psychosocial factors and mental illness associated with sexual offending. Adequate care, treatment and rehabilitation of sexual offenders are crucial to reduce the impact of sexual offence and re-offending. AIMS: To determine the demographic variations, clinical factors, and observation outcomes in terms of diagnosis, fitness to stand trial, and criminal responsibility among the alleged sexual offenders referred to Thabamoopo Hospital. OBJECTIVES: To determine the prevalence of mental disorders among alleged sexual offenders, to determine the number of offenders fit or unfit to stand trial and who are criminal or not criminally responsible, to determine factors associated with vulnerability to sexual offending behaviour. METHOD: This study is based on a review of clinical records and files and psychiatrists' observation reports of all alleged sexual offenders referred by the courts for forensic psychiatric observation between the period January 2015 to December 2018 at Thabamoopo Hospital. RESULTS: The sample consists of 94 participants, only one female; all were black Africans. The majority were in middle adulthood, unemployed, of a lower level of education and not married. All participants had been charged with rape. A large number of the alleged sexual offenders were diagnosed with mental conditions. The most common diagnoses were Intellectual disability disorders, psychotic disorders and substance-related disorders. More than half of the sample was fit to stand trial and criminally responsible. CONCLUSION: More than half of the participants charged with rape were found fit to stand trial and to be criminally responsible. A significant number were diagnosed with mental illness. The outcomes of being unfit to stand trial and not being criminally responsible were common among mentally ill sexual offenders. The results signify that this group of offenders needs adequate psychiatric care, treatment and rehabilitation in order to reduce sexual offending and re-offending due to the impact of mental illness.
Thesis (M. Medicine (Psychiatry)) -- University of Limpopo, 2022
Keywords: Sexual offence crimes; Sexual offenders; Women; Children; Forensic psychiatric observation; Forensic psychiatry -- South Africa -- Limpopo; Sex offenders -- South Africa -- Limpopo; Sex offenders -- Psychology